Novel biomarkers for primary biliary cholangitis to improve diagnosis and understand underlying regulatory mechanisms. (15th May 2019) - Bombaci, Mauro; Pesce, Elisa; Torri, Anna; Carpi, Donatella; Crosti, Mariacristina; Lanzafame, Manuela; Cordiglieri, Chiara; Sinisi, Antonia; Moro, Monica; Bernuzzi, Francesca; Gerussi, Alessio; Geginat, Jens; et al.
Abstract: Background and aims: Primary biliary cholangitis is an autoimmune biliary disease characterized by injury of bile ducts, eventually leading to cirrhosis and death. In most cases, anti‐mitochondrial antibodies and persistently elevated serum alkaline phosphatase are the basis for the serological diagnosis. Anti‐nuclear antibodies are also useful and may indicate a more aggressive diseases course. In patients in which anti‐mitochondrial antibodies are not detected, an accurate diagnosis requires liver histology. This study aims at identifying specific biomarkers for the serological diagnosis of primary biliary cholangitis. Methods: Sera from patients affected by primary biliary cholangitis, primary sclerosing cholangitis, hepatitis C virus (with and without cryoglobulinemia), hepatocarcinoma and healthy donors were tested on a protein array representing 1658 human proteins. The most reactive autoantigens were confirmed by DELFIA analysis on expanded cohorts of the same mentioned serum classes, and on autoimmune hepatitis sera, using anti‐PDC‐E2 as reference biomarker. Results: Two autoantigens, SPATA31A3 and GARP, showed high reactivity with primary biliary cholangitis sera, containing or not anti‐mitochondrial antibodies. Their combination with PDC‐E2 allowed to discriminate primary biliary cholangitis from all tested control classes with high sensitivity and specificity. We found that GARP expression is upregulated upon exposure to biliary salts in human cholangiocytes, an event involving EGFR and insulin pathways. GARP expression was also detected in biliary duct cells of PBC patients. Conclusions: This study highlighted SPATA31A3 and GARP as new biomarkers for primary biliary cholangitis and unravelled molecular stimuli underlying GARP expression in human cholangiocytes.